2013
DOI: 10.1038/cti.2013.11
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial lipodipeptide, Lipid 654, is a microbiome‐associated biomarker for multiple sclerosis

Abstract: Multiple sclerosis (MS) is an autoimmune disease of unknown etiology. Infectious agents have been suggested to have a role as environmental factors in MS, but this concept remains controversial. Recently, gastrointestinal commensal bacteria have been implicated in the pathogenesis of autoimmune diseases, but mechanisms underlying the relationship of human systemic autoimmunity with the commensal microbiome have yet to be identified. Consistent with the lack of understanding of pathogenic mechanisms and relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
96
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(101 citation statements)
references
References 20 publications
5
96
0
Order By: Relevance
“…We have previously reported that L654, a microbiome-derived TLR2 ligand, can be identified in the serum of all healthy individuals, but is significantly lower in the serum of MS patients (1). L654 stimulates cells through TLR2, does not stimulate through TLR4, and fails to stimulate in the absence of TLR2 (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously reported that L654, a microbiome-derived TLR2 ligand, can be identified in the serum of all healthy individuals, but is significantly lower in the serum of MS patients (1). L654 stimulates cells through TLR2, does not stimulate through TLR4, and fails to stimulate in the absence of TLR2 (16).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, L654 is recovered in significantly lower levels in the serum of patients with MS (1). Although pathogenassociated molecular patterns such as L654 are normally thought of as proinflammatory, we asked whether a decrease in TLR2 ligands could have relevance to the disease pathogenesis of MS.…”
mentioning
confidence: 99%
“…This may relate to Lipid 654, a bacterially derived lipodipeptide that is produced by a number of Bacteroidetes and was found to have lower serum levels among MS patients compared to controls. 13,19 Lipid 654 binds toll-like receptor 2 (TLR2); although TLRs are critical to innate immune system activation, low-level tonic TLR2 stimulation by Lipid 654 has been shown to regulate innate immune responses. 19,20 Propionate is a short-chain fatty acid (SCFA) with antiinflammatory effects that is produced by some Bacteroidetes, and reduced propionate-producing Bacteroidetes may promote inflammation.…”
Section: Bacteroidetesmentioning
confidence: 99%
“…13,19 Lipid 654 binds toll-like receptor 2 (TLR2); although TLRs are critical to innate immune system activation, low-level tonic TLR2 stimulation by Lipid 654 has been shown to regulate innate immune responses. 19,20 Propionate is a short-chain fatty acid (SCFA) with antiinflammatory effects that is produced by some Bacteroidetes, and reduced propionate-producing Bacteroidetes may promote inflammation. [21][22][23] Bacteroides fragilis-derived polysaccharide A (PSA) may induce IL-10-dependent enhanced conversion of CD4+ T-regulatory cells and protect against autoimmunity in MS. 24,25 Oral administration of Parabacteroides distasonis may augment the CD4+ T-regulatory phenotype, plausibly linking its depletion in MS pathogenesis.…”
Section: Bacteroidetesmentioning
confidence: 99%
“…Lipid 654 from commensal bacteria inhabiting the gastrointestinal tract and the oral cavity is present in the systemic circulation [21]. Interestingly, serine dipeptide lipids may also promote alveolar bone loss in periodontitis by inhibiting osteoblast differentiation [22].…”
mentioning
confidence: 99%